The cash conversion cycle - McDonald, Michael (Henry Stewart Talks, 2019)
Cash flows, Budgeting, Cash Conversion Cycle, Estimating cash flows, Compounded Annual Growth Rates (CAGR), Market share, Sales, Expenses